2021
DOI: 10.1371/journal.pone.0258704
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vaccination against SARS-CoV-2 infection and Covid-19 hospitalisation among Finnish elderly and chronically ill—An interim analysis of a nationwide cohort study

Abstract: Background In Finland, both mRNA and adenovirus vector (AdV) Covid-19 vaccines have been used after the vaccination campaign started on December 27, 2020. Vaccination of the elderly and chronically ill was prioritized and the interval between doses set to 12 weeks. The objective of this interim analysis was to evaluate first and second dose vaccine effectiveness (VE) in a real-world setting. Methods During the first five months of the campaign, a register-based cohort study was conducted in the Finnish elder… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…We used the data in the Care Register for Health Care from 2015 onwards to count the number of nights hospitalized between 2015 and 2019 and to assess the presence of comorbidities that predispose to severe Covid-19 according to a recent study of predictors of Covid-19 hospitalization [26]. We completed the collection of data on predisposing comorbidities with primary health care records and prescription data as described in a previous study [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the data in the Care Register for Health Care from 2015 onwards to count the number of nights hospitalized between 2015 and 2019 and to assess the presence of comorbidities that predispose to severe Covid-19 according to a recent study of predictors of Covid-19 hospitalization [26]. We completed the collection of data on predisposing comorbidities with primary health care records and prescription data as described in a previous study [3].…”
Section: Methodsmentioning
confidence: 99%
“…The elderly are highly vulnerable to severe coronavirus disease 2019 (Covid-19) (1) and, therefore, protecting them is essential to reduce the disease burden caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Covid-19 vaccinations prevent SARS-CoV-2 infections and decrease the number of Covid-19 hospitalizations in a population (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the median protection duration of the primary COVID-19 vaccinations was longer among those aged 60 years and older compared with other age groups (adolescents and adults). Several studies revealed that BNT162b2, Moderna, and ChAdOx1 vaccines’ effectiveness are high among elderly individuals [ 12 , 15 , 16 ]. A common explanation for these outcomes is the priority of vaccine administration among elderly individuals as they are considered a high-risk group for COVID-19, and they could be less exposed to infection by staying at home.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and reports from other outbreaks in nursing homes 16,17 confirm the possibility of SARS-CoV-2 spread in nursing homes even when most residents are vaccinated. Others have reported that although vaccine effectiveness (VE) against infection by SARS-CoV-2 variants is remarkably decreased, [18][19][20][21] VE against severe illness remains high after two doses. 18,[21][22][23] Among all infected residents in the two LTFCs four residents died after having tested positive for COVID-19, but only one death was ruled to have been caused by COVID-19 with certainty.…”
Section: Igg Antibody Levels and Nab Titers Of Twice Vaccinated And I...mentioning
confidence: 99%
“…Others have reported that although vaccine effectiveness (VE) against infection by SARS-CoV-2 variants is remarkably decreased, [18][19][20][21] VE against severe illness remains high after two doses. 18,[21][22][23] Among all infected residents in the two LTFCs four residents died after having tested positive for COVID-19, but only one death was ruled to have been caused by COVID-19 with certainty. Due to our small sample size and deaths with unclear relation to COVID-19 we were unable to assess VE.…”
Section: Igg Antibody Levels and Nab Titers Of Twice Vaccinated And I...mentioning
confidence: 99%